Flowering synchronization and panicle elongation of cytoplasmic male sterile rice lines during seed multiplication - Hashim, Shahida (2019)
Rice (Oryza sativa L.) is a staple food of most Malaysia because it has good source of energy that contains nutrients, vitamins and minerals. It is estimated that Malaysia population will increase to 43 million in 2050 thus; rice production needs to be increased too. Producing hybrid rice is one of the options that can be considered because it has been successfully adopted in most of rice producer countries in Asia such as China, Thailand, Vietnam and India. Hybrid rice needs to be produced for growers to plant. However, poor cross-pollination or out-crossing between parental lines is the major constraint in hybrid rice seed production. The low out-crossing is due to poor flowering synchronization between parental lines and also poor panicle exsertion of cytoplasmic male sterile (CMS) line. Improper flowering synchronization may reduce number of seed set because probabilities of floret to be out-crossed during flowering period are low. Hence, the objectives of this study was to improve the out-crossing rate and increase the grain yield of the multiplied CMS during CMS seed multiplication through utilization of seeding date interval for proper flowering synchronization and application of exogenous gibberellic acid to improve the panicle exsertion rate of the CMS. In the first study, floral traits and flowering behaviours of two locally developed CMS and maintainer lines were observed namely 0025A/0025B and 0047A/0047B. The observation shows that the female reproductive parts of 0025A CMS lines such as stigma length, stigma breadth and stigma area were 30.32-69.50% longer, 80-140% wider and 135.1-217.4% larger than 0025B maintainer. Stigma length, stigma breadth and stigma area of 0047A CMS were also 83.3-100% longer, 147.6-152.6% wider and 8.7-31.6% larger than 0047B maintainer. These characteristics are essential because more pollen grains are expected to be deposited on the stigma of the CMS. The 0025B maintainer had 34.0-177.86% longer filament than their respective CMS thus indicating that long filament increased the possibilities of pollen grains to deposit on the stigma. The on-set of flowering of 0025A CMS and 0025B maintainer was 63-69 and 63-67 days after transplanting (DAT), respectively, thus indicating that the flowering period of both parental lines may be synchronized and the seed can be sown concurrently. However, the on-set of flowering between 0047A CMS and 0047B maintainer was significantly different (P<0.05). Hence, staggered sowing needs to be done for these two parental lines in order to get proper flowering synchronization. Six seeding date intervals were implemented on the maintainer lines in order to get proper flowering synchronization between parental lines. Result shows that sowing the 0025B maintainer at 2 days prior and 6 days after the CMS was sown significantly reduced the number of tillers per sq m by 18.99-20.39 and 13.17-17.94%, respectively. The grain yield was also decreased by 20.59-45.83 and 127.78-150.00% when the 0025B maintainer was sown at 2 days prior and 6 days after the 0025A CMS was sown, respectively. The 0047B maintainer has to be sown at 4 and 6 days after the 0047A CMS was sown because these seeding date interval significantly affected the number of tillers per sq m, out-crossing rate, grain yield and harvest index of the 0047A CMS (P<0.05). Four concentrations of gibberellic acid (GA3) were applied to both CMS and maintainer lines when 10% of the panicles emerged out from the sheath. Result shows that application of GA3 at the concentrations of 15, 30 and 45 mg/L significantly improved the plant height of 0025A CMS by 7.8-13.7, 10.8-17.0 and 13.9-16.5%, respectively. The grain yield of 0025A CMS was also increased by 71.4-433.3, 450.0-500.0 and 116.5-125.0%, respectively. Selected seed qualities such as germination rate and germination index of 0025A CMS were also improved by 48.77-97.53 and 100-150%, respectively, as GA3 at the concentrations of 15, 30 and 45 mg/L were applied to the plants. Application of GA3 was found affecting some of the changes in the internode of the CMS. Forty five mg/L GA3 is not recommended to be used in CMS seed multiplication because it is related to lodging incidence. Information on the floral traits and flowering behaviours of the CMS and maintainer lines may be useful for the breeders and rice physiologist to improve certain traits of the parental lines. An appropriate concentration of GA3 found in this study may be adopted by industry takers such as seed producer in order to minimize the cost with better yield performance.